Hubungan Antara Fungsi Biaya dan Keberlanjutan dalam Operasional Perusahaan - Muhammad Irwan Firmansyah (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
Cost-Volume-Profit (CVP) analysis is a crucial financial management tool that aids companies in strategic decision-making. This study aims to identify the role of CVP analysis in the digital era and how technology integration can enhance its effectiveness. Using a qualitative approach through case studies in several companies, the research reveals that the utilization of big data, predictive analytics, and analytical software can improve decision-making accuracy and speed. The findings indicate that companies successfully adopting digital technology in CVP analysis can significantly enhance profitability and operational efficiency. However, challenges such as data quality and rapid changes in the business environment remain obstacles that need to be addressed. Therefore, investment in technology and human resource training is a crucial step in optimizing the benefits of CVP analysis in the digital era.